Patient, thyroid, and surgeon related factors that make thyroidectomy difficult-cohort study - Bothra, Sapana (Ann Med Surg (Lond), 2019)
INTRODUCTION: When thyroidectomy is performed under optimal conditions within a milieu of sound anatomical and physiological knowledge combined with meticulous surgical skills, complications are minimal. However, thyroidectomy can be difficult, and its complications can be life-threatening. The factors that predict difficult thyroidectomy can be patient-, thyroid-, or surgeon-related, and we aimed to study these three factors. . MATERIALS AND METHODS: This prospective study was performed in a tertiary care center between September 2016 and March 2017. We developed and validated modified thyroidectomy difficulty scale (TDS), with 11 items. Preoperatively, height, weight, neck length, and other parameters were recorded. Postoperatively, the modified TDS form was filled out by the surgeon and assistant, blinded to each other's responses. The minimum score was 19 and maximum was 54. The surgeon's baseline pulse rate was monitored throughout the procedure using a pulse oximeter probe that was On-The-Go (OTG) compatible. The probe was placed over the ear lobule/pinna of the surgeon and connected to an Android phone that was comfortably placed in the surgeon's pocket inside the gown. An application USB SPO(2), was used in recording the pulse rate. RESULTS: A total of 52 patients undergoing hemi- or total thyroidectomy were included in this study. All had benign cytology on fine needle aspiration cytology (colloid, 71.42%). A total of 104 modified TDS questionnaires filled by the operating surgeon and assistant were analyzed. The pulse rate of the operating surgeon, as measured by the novel pulse oximeter, was recorded in 52 surgeries. The minimum score was 20, maximum score was 35.50, and mean score was 26.85 ± 2.80. There was an interobserver agreement in most domains of the modified TDS except mobility. The surgeon was found to have the maximum heart rate when performing recurrent laryngeal nerve (RLN) dissection in 38 patients (73.07%). DISCUSSION: We found that majority of the trainees found thyroidectomy to be a vigorously intense activity. Thyroidectomy is a demanding surgery, which requires meticulous identification and dissection of the RLN and parathyroid glands for optimum outcome.